Surgical Treatment of Jugular Foramen Schwannoma: Surgical Treatment Based on a New Classification. Issue 3 (12 June 0015) - Samii, Madjid; Alimohamadi, Maysam; Gerganov, Venelin
Abstract: BACKGROUND: Surgery plays a crucial role in the management of jugular foramen schwannomas (JFSs). Still, it remains challenging, particularly in cases of tumor growth inside the bony canal of the jugular foramen (JF). OBJECTIVE: To present our recent experience with surgical treatment of JFSs, with particular focus on the efficacy and safety of the endoscope-assisted retrosigmoid infralabyrinthine and transcervical approaches for tumors extending through the JF bony canal. METHODS: Sixteen consecutive patients with JFSs were retrospectively evaluated. Tumor extension was classified using a modification of our previous classification, and surgical approach was selected accordingly. The extent of tumor resection, cranial nerve outcome, approach-related morbidities, and recurrence of the tumors were documented. RESULTS: Four cases of JFSs were subtotally resected elsewhere and 12 were primary. The most common type was B2 (6 cases). The average tumor size was 38.5 mm. Gross total resection was achieved in all patients, and none recurred during follow-up. There was no operative mortality or new permanent neurological deficits. A postoperative cerebrospinal fluid leak developed in 2 patients, 1 managed with lumbar drain and the other with wound revision. The preoperative swallowing difficulty temporarily deteriorated in 3 patients, but recovered well within the first 2 postoperative weeks in all 3. Improvement of the preoperative lower cranial nerve dysfunction was observed in 5 patients. CONCLUSION: The surgical approach selection to JFSs should be tailored individually to their extension pattern. The judicious application of endoscope-assisted retrosigmoid infralabyrinthine and transcervical techniques allow for safe and more radical removal of JFSs with a major intraosseous part.